(3eLehY COHjs
(3ChdgG (B:s
(3ef ebOeI cJGH bhdg(B: (3GdMeO ddg GdPj TQM UOQ ef JCOH, hQaY bOQ ef JCgd ddYhd hJCgH s
(3BNQgG (B:s
(3hde JdJaJ EP CgQbJ OeYgG OeG hdh aYd GdCYOG HfaSc HYV eG s
(3HYV ChQGbgG JfJej Edj CcKQ ef cJGHs
(3hGdQGLM Cf ChQGbgG GdeJfGKQI LeYJ Ohf JQJjHs
(3TYQ hfKQs
(3haj GdUaMI GdJGdjI YfhGf cJGH BNQ hgh(B: (3GdeNJGQ ef Yjhf TYQ GdTYQGA GdehqdOjf, hge MHjH Hf ChS, GdHMJQj, CHhfhGS, GHf GdQhej s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdCOHs